2003
DOI: 10.1103/physreve.67.021402
|View full text |Cite
|
Sign up to set email alerts
|

Field-induced structures in miscible ferrofluid suspensions with and without latex spheres

Abstract: We explore magnetic-field-induced ordering and microphase separation of aqueous ferrofluid and of aqueous mixtures of ferrofluid with nonmagnetic latex spheres. The ferrofluid is a surfactant stabilized aqueous suspension of magnetite (Fe3O4) particles with average diameter 20 nm (including the approximately 2.5-nm thick surfactant layer); the nonmagnetic latex spheres are charge stabilized polymethylmethacrylate (PMMA) particles with diameters of 42 nm, 108 nm, and 220 nm. In the presence of a uniform magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 32 publications
3
56
0
Order By: Relevance
“…The bulk aggregates have sizes of about 1 µm; they have repeatedly been observed with ordinary micro scopes (see, e.g., [5][6][7]). Since the sizes of particles in common ferrofluids are smaller than the visible light wavelength, their linear chains cannot be registered by the optical methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk aggregates have sizes of about 1 µm; they have repeatedly been observed with ordinary micro scopes (see, e.g., [5][6][7]). Since the sizes of particles in common ferrofluids are smaller than the visible light wavelength, their linear chains cannot be registered by the optical methods.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it is well known that, when the energy of the magnetic interparticle interactions in ferrofluids markedly exceeds thermal energy kT, the particles can form linear chains or dense bulk droplet shaped aggregates (see, e.g., [5][6][7][8][9]). …”
Section: Introductionmentioning
confidence: 99%
“…In order to deter mine the latter quantity, expressions (3) have to be substituted into conditions (2). The first relation (3) readily yields (4) Denoting the total number of particles in a fork by n = i + j + k + 3, we obtain the following expression for the volume fraction of forks: (5) Analogous considerations lead to the relation…”
Section: Main Assumptions and Statistical Modelmentioning
confidence: 99%
“…Numerous experiments have shown that particles in ferrofluids are capable of forming various heteroge neous structures such as linear chains, closed rings, Y like forks, and dense droplets [1][2][3][4][5][6]. These struc tures have a typical size of several microns, and they can be readily observed with common optical micro scopes.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known (see, for example, refs. [11][12][13][14][15][16][17]) that magnetic field stimulates the phase condensation in ferrofluids, although only the biggest particles of polydisperse ferrofluid interact strongly enough to undergo the phase condensation.…”
Section: Theoretical Modelmentioning
confidence: 99%